Медиумската етика и слободата на изразување - Македонскиот медиумски простор - Донев, Дејан (Правен факултет „Јустинијан I“, Скопје, 2012)
When we talk about professional, i.e deontological standards and their real practice in the Macedonian journalism and media, viewed from an ethical aspect, a general conclusion can be conducted that it is very hard to be applied and practiced what is a main democratic characteristic in democratic society – freedom of speech, as one of the central rights, from which existence, or non-existence greatly depends the accomplishment of the other political rights, respectively, the pre-condition for enjoyment of many rights and freedoms enshrined in the European Convention on Human Rights. Especially if taking into account the recent "shocks" in our media space. Yet, the thesis that journalism in Macedonia does not exist, is quite exaggerated, because journalism, without any doubt, is an unavoidable characteristic and part of any democratic society. Indeed, the degree of democratization of the relations inside one society, it can be measured through the development and freedom of journalism. Hence, saying that journalism in Macedonia is in very bad condition, we already gives a very realistic statement and facts that can be validated in the Macedonian media space. Why is that so and how can the situation be improved? How did we came to this unbearable situation? The text deals with the ethical analysis of the main causes for this situation of freedom of speech in the media space in R. Macedonia, trying to answer the question "what kind of ethics and ethical behavior is needed" as a rehabilitation and future preventive in circumstances when there is a general freedom of speech, but no freedom of thought, i.e when there is a freedom of speech, but there is no, it does not exist, a culture of expression and listening. In addition to the latter, and the ranking of Macedonia on the 94th place in the last report of Reporters without borders.
Media ethics & freedom of speech - Macedonian media space
Годишник на Правниот факултет „Јустинијан Први“ во Скопје, Том 44-46, по повод 35 години од основањето на студиите по новинарство на Правниот факултет во Скопје.